2024
DOI: 10.3389/fpls.2023.1279019
|View full text |Cite
|
Sign up to set email alerts
|

Potentially suitable habitats of Daodi goji berry in China under climate change

Jianling Li,
Changrong Deng,
Guozhen Duan
et al.

Abstract: IntroductionGoji berry (Lycium barbarum L.) is a famous edible and medicinal herb worldwide with considerable consumption. The recent cultivation of goji berries in the Daodi region was seriously reduced due to increased production costs and the influence of policy on preventing nongrain use of arable land in China. Consequently, production of Daodi goji berry was insufficient to meet market demands for high-quality medicinal materials. Searching for regions similar to the Daodi region was necessary.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…We found that the expansion-suitable regions were mainly distributed in the northeast and northwest of the current ranges. This phenomenon of thermophilic plants expanding towards higher latitudes in response to climate warming has been widely documented, with examples including Lycium barbarum L. [45], Litsea cubeba (Lour.) Pers [46], and Agastache rugosa (Fisch.…”
Section: Habitat Distribution Under Climate Changementioning
confidence: 99%
See 4 more Smart Citations
“…We found that the expansion-suitable regions were mainly distributed in the northeast and northwest of the current ranges. This phenomenon of thermophilic plants expanding towards higher latitudes in response to climate warming has been widely documented, with examples including Lycium barbarum L. [45], Litsea cubeba (Lour.) Pers [46], and Agastache rugosa (Fisch.…”
Section: Habitat Distribution Under Climate Changementioning
confidence: 99%
“…The topsoil data were obtained from the World Soil Database (Harmonized World Soil Database v1.2, http://www.fao.org/soilsportal/, assessed on 16 January 2024) and converted to ASCII format using ArcGIS, which contained 17 soil variables. Due to lack of future soil data, the future soil layers were considered to be consistent with the current over such a short time frame in this study [45].…”
Section: Acquisition and Processing Of Chili Pepper Distribution Poin...mentioning
confidence: 99%
See 3 more Smart Citations